A fluorescence-activatable tumor-reporting probe for precise photodynamic therapy. Issue 29 (13th July 2021) - Li, Jian; Wang, Tingting; Jiang, Feng; Hong, Zhangyong; Su, Xinhui; Li, Shuang; Han, Shoufa
Abstract : Approaches that could enable precise photodynamic therapy (PDT) are of therapeutic potential. Abstract : Approaches that could enable precise photodynamic therapy (PDT) are of therapeutic potential. We herein report a trifunctional probe (Glu-RdEB ) that could be activated to generate fluorescent rhodamine species to pinpoint tumor foci. The probe contains a γ-glutaminyl moiety cleavable to γ-glutamyl transpeptidase (GGT) overexpressed in multiple tumors, an entity of an ENBS photosensitizer for PDT, and an entity of rhodamine fluorescently quenched by ENBS. Upon activation by tumor-associated GGT, the probe releases highly fluorescent rhodamine that is selectively confined in tumors whereby light irradiation leads to effective tumor regression in mice. These results indicate the feasibility of a fluorescently quenched dye–photosensitizer pair to yield tumor-activatable fluorescence to direct PDT.